Exploring the molecular mechanism of OsROS1a in regulating resistance to bacterial leaf streak through transcriptome and DNA methylation profiling in rice (Oryza sativa L.) - Xiaofang Xie; Xuansong Yang; Libin Lu; Tong Li; Mingyue Qin; Huazhong Guan; Yan Zheng; Tao Lan; Weiren Wu (BMC Genomics)
Abstract Background DNA demethylases regulate the levels of genomic DNA methylation in plants. The demethylase REPRESSOR OF SILENCING 1 (ROS1) is a crucial factor for modulating gene expression in plant disease responses. Bacterial leaf streak (BLS), caused by Xanthomonas oryzae pv. Oryzicola (Xoc), is a highly destructive disease in rice. BLS resistance in rice is known to be quantitatively inherited, but the mechanisms by which DNA methylation controls BLS resistance remain poorly understood. Results In this study, we knocked down OsROS1a expression in the rice variety Nipponbare using RNA interference (RNAi). The average BLS lesion length in the transgenic (T2) OsROS1a-RNAi (RS) lines was significantly reduced compared to that in wild-type Nipponbare plants (NP). Using whole-genome bisulfite sequencing (WGBS) and RNA-sequencing (RNA-seq), we analyzed the DNA methylations and transcriptomes of RS lines in comparison with NP at 0 (control), 5, 10, and 24 h post-inoculation with Xoc. A total of 1080 differentially expressed genes (DEGs) related to Xoc infection between the NP and RS lines were identified, which could be grouped into 8 clusters by K-means analysis. The DEGs in cluster 1 were enriched in the biological process related to defense response, response to stress, oxidation-reduction, etc. Integration of the methylome and transcriptome data revealed 112 overlapping differentially methylated and expressed genes (DMEGs). Gene Ontology (GO) analysis showed that the DMEGs were mainly involved in biological processes, such as metabolic process, cellular process, responses to stimulus, signaling, and immune system processes. KEGG pathway enrichment analysis revealed that these DMEGs were enriched in pathways related to glutathione metabolism, plant-pathogen interaction, cysteine and methionine, diterpenoid biosynthesis, photosynthesis, and starch and sucrose. Additionally, LOC_Os09g12660, encoding the glucose-1-phosphate adenylyl transferase large subunit, a chloroplast precursor involved in synthesizing activated glycosyl donor, showed strong potential to contribute to BLS resistance. Conclusion OsROS1a plays a crucial role in modulating rice resistance to bacterial leaf streak (BLS) caused by Xanthomonas oryzae pv. oryzicola (Xoc). These findings provide valuable insights into the role of OsROS1a in BLS resistance.